The Historical Transformation of Arabic in the Multilingual Landscape of the Muslim Community of Tidore Island - Agustang Kallang; Sugirma Sugirma; M. Risal Abdullah; Iman Yamin (LPPM Universitas KH.A. Wahab Hasbullah, 2026)
This study examines the historical transformation of the Arabic language in the multilingual landscape of the Muslim community on Tidore Island, North Maluku. This study aims to understand how Arabic interacts with local and immigrant languages, as well as its role in the traditions, education, and social identity of communities. The research method uses a qualitative approach with ethnography and literature studies, as well as data collection through documents, interviews, and field observations. The results of the study show that Arabic was originally present as a ritual and religious language, used in prayers, manuscript texts, as well as naming terms and regions. Over time, this language has undergone a transformation into a means of communication, education, and social identity, which is strengthened through formal and non-formal educational institutions such as madrassas and pesantren. The interaction of Arabic with Tidore, Makian, Ternate, and immigrant languages creates a distinctive multilingual landscape, where Arabic becomes an integral part of people's social and cultural lives. These findings confirm that Arabic is not only a religious heritage, but also a social and cultural agent that shapes the linguistic dynamics and traditions on Tidore Island. This research opens up opportunities for further studies on language adaptation, language contact, and the development of Arabic language learning based on local culture in multiethnic areas.